IDENTIFIKASI PEMBELAJARAN MATEMATIKA DIMASA PANDEMI COVID-19 PADA SMP NEGERI SOKORIA - Yulius Wilfridus; Stefanus Notan Tupen; Maria Fatima Mei (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2021)
This study aims to (1). To find out the process of learning mathematics during the Covid-19 pandemic. (2). To find out what the headmaster was doing in learning mathematical during the Covid-19 Pandemic. The research method used is using descriptive qualitative research method. Data collection techniques used interview techniques and documentation. The subject in this research is the principal, mathematics teacher and four students who are randomly selected. The results obtained from this study indicate (1). The process of learning mathematics during the Covid-19 pandemic described modules or material summaries and assigning assignments to student. (2). To see what the headmaster did in learning mathematical during the Covid-19 pandemic. Thus suggested that teachers should able to prepare the material properly so that students do not get bored with online learning. Students must take advantage of their free time to always explore the material that the teacher has distributed. For subsequent researchers who conduct research related similar, we use a broader subject.